Uso de biofertilizante y sus efectos en las características agronómicas y rendimiento de Brassica olerácea L. col repollo, var. Fuyutokio, Zungarococha-Loreto.2022 - Montero Vilchez, Nilton Jesus (2023)
Cabbage var. Fuyutokio is a vegetable of good size and head weight that exceeds 1,600 g, which is very interesting to grow in the area, using locally manufactured biofertilizer based on the composting of manure and remains of laying birds plus beneficial microorganisms, of which the study was carried out in an area located in Zungarococha, south of Iquitos, using progressive amounts of the biofertilizer and then determine its effects on cabbage characteristics and performance. The results were analyzed through the DBCA Statistical Design, p-value and the Tukey Test, concluding in the following: The incorporation of progressive amounts of the biofertilizer increased the yield of the crop. Plant height, stem weight, root length and weight, head diameter and plant weight were increased as more biofertilizer was added. Plant width, number of leaves/plant, stem length remained uniform in the quantities of 30 and 40 t of biofertilizer/ha. The incorporation of 40 t / ha of biofertilizer in the crop, invoiced an economic income of S/.29,860.00